2020
DOI: 10.1186/s12955-020-01558-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and quality of life in seborrheic dermatitis patients: a cross-sectional study in China

Abstract: Background Seborrheic dermatitis (SD) is a common, chronic, inflammatory skin disorder, yet few studies have reported its clinical characteristics, or addressed its effect on quality of life (QoL). This study assesses the clinical characteristics and QoL of SD patients in China. It also identifies the clinical, demographic and environmental factors that may influence QoL. Methods Three hundred twelve SD outpatients from 9 hospitals c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
0
14
0
2
Order By: Relevance
“…SD may affect the sebaceous glands in areas such as the face and scalp and is mainly treated by the use of antifungal agents. Since short term treatment anti-inflammatory drugs (such as topical corticosteroids) may have side effects and are only used in the short term ( Clark et al., 2015 ), the improvement of modifiable lifestyle factors may help reduce the burden of disease ( Sanders et al., 2019 ) Furthermore, approximately 50% of SD patients in China have serious emotional problems, which may substantially affect their quality of life ( Xuan et al., 2020 ). This warrants global public health attention to SD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SD may affect the sebaceous glands in areas such as the face and scalp and is mainly treated by the use of antifungal agents. Since short term treatment anti-inflammatory drugs (such as topical corticosteroids) may have side effects and are only used in the short term ( Clark et al., 2015 ), the improvement of modifiable lifestyle factors may help reduce the burden of disease ( Sanders et al., 2019 ) Furthermore, approximately 50% of SD patients in China have serious emotional problems, which may substantially affect their quality of life ( Xuan et al., 2020 ). This warrants global public health attention to SD.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study also showed that men with light and dry skin are more likely to suffer from SD ( Sanders et al., 2018 ). However, a study of data from outpatients in nine hospitals in China found that 67.3% of SD patients were female ( Xuan et al., 2020 ). The ASIR and ASDR of SD showed an increasing trend for both males and females from 1990 to 2019.…”
Section: Resultsmentioning
confidence: 99%
“…Various predisposing variables, such as fungus colonization and Sebaceous gland activity plus a number of other variables that determine an individual's vulnerability, have been discovered in investigations. Several lines of evidence point to Malassezia yeasts playing a pathogenic role in SD [4,5]. Malassezia are lipophilic yeasts found mostly in seborrheic areas of the body.…”
Section: Introductionmentioning
confidence: 99%
“…In cases of pityriasis capitis simplex, squams and pruritus on the scalp are the most basic clinical findings. This clinical state significantly affects the quality of life in this patient group and causes the development of emotional problems such as impaired self-esteem 5 . In the USA, people spent 300 million dollars annually on "over-the-counter" products to relieve the complaints of squams and pruritus on the scalp 2 .…”
Section: Introductionmentioning
confidence: 99%